(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
Parent training is fundamental in the psychotherapy of children and adolescents. It is up to the fathers/mothers/caregivers to manipulate the contingencies that act on the target behaviors of children and adolescents in therapy, in this way, they can also be users of psychotherapy services. It is common in parent training programs to use strategies based on instructional control, which can lead to dependence of fathers/mothers/caregivers on the psychologist. Pragmatic Behavioral Psychotherapy – PCP is a behavioral-analytical therapy model for adults that is characterized by interventions in which instructional control is avoided, applying procedures such as reflective questioning. This article describes how the PCP can be applied to parent training, in order to favor greater autonomy of fathers/mothers/caregivers in the development of more effective parenting practices in raising children.